2018
DOI: 10.7326/aitc201803060
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care

Abstract: Palliative care prioritizes symptom management and quality of life throughout the course of serious illness. Regardless of whether care is inpatient or outpatient, primary or subspecialty, a solid understanding of the basics of effective communication, symptom management, and end-of-life care is crucial. This article reviews these essentials and provides an overview of current evidence to support patient-centered palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Palliative care (PC) is an interdisciplinary type of specialized care focused on improving or maintaining quality of life for patients with a serious illness and for their families. 1 Hospice is a subset of PC for patients with more advanced serious illness and an expected survival of less than 6 months. Upstream from hospice care, PC does not have prognosis or disease severity requirements and aims to be included in care from the time of diagnosis onward.…”
Section: Introductionmentioning
confidence: 99%
“…Palliative care (PC) is an interdisciplinary type of specialized care focused on improving or maintaining quality of life for patients with a serious illness and for their families. 1 Hospice is a subset of PC for patients with more advanced serious illness and an expected survival of less than 6 months. Upstream from hospice care, PC does not have prognosis or disease severity requirements and aims to be included in care from the time of diagnosis onward.…”
Section: Introductionmentioning
confidence: 99%
“…[12] However, one can deduce that admissions, complications, and costs relating to noncancer-related illnesses far outweigh that of cancer-related illnesses. [34] Determination of whether noncancer illnesses are terminal is dependent on illness and patient-related factors;[56] however, this study showed there is marked variability among medical professionals as to what point these illnesses become terminal. Frequent hospitalization as a red flag[5] is also not appreciated among medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…As perverse as this may sound, the incentives generated by the fee-for-service payment system may also be a realistic barrier (not highlighted in this study) as the implementation of palliative specialty care may inadvertently reduce revenue. [26712] This not only adds to the fear but can also lead to medical management that is not tailored to the patient's needs.…”
Section: Discussionmentioning
confidence: 99%
“…Los CP buscan atender, de forma activa y holística, a los pacientes de todas las edades con enfermedades crónicas, que generan sufrimiento debido a su severidad, y con mayor intensidad en aquellos que se encuentran cerca del final de la vida. Lo que se busca es mejorar su calidad de vida, la de sus familias y cuidadores, a través de un equipo multidisciplinario conformado por médicos, enfermeros, psicólogos, trabajadores sociales y asesores espirituales (2,3) .…”
Section: Introductionunclassified